PENGARUH CITRA MEREK, HARGA DAN KUALITAS PRODUK TERHADAP MINAT PEMBELIAN ULANG KOSMETIK PT. PARAGON TECHNOLOGY AND INNOVATION - Desi Sari Fatmalawati; Ana Noor Andriana (JMB : Jurnal Manajemen dan Bisnis, 2021)
The Influence of brand image, price and product quality on PT. Paragon Technoogy and Innovation. This research was conducted on a business administration student at Mulawarman University who had purchased cosmetics.This study aims to examine the effect of brand image, price and product quality on cosmetic repurchase interests. Data distributing questionnaires to 116 respondents. The sampling technique used is non probability sampling (accidental sampling). The data obtained were analyzed using multiple linear regression techniques with the help of statistical software SPSS version 23. The brand image variable partially has no effect and is insignificant to the repurchase interest, Price partially has a negative and not significant effect on repurchase interest and the quality product variable partially has a significant effect on repurchase interest and is the most powerful or dominant variable.Suggestions to increase repurchase interest is to maintain product quality.Brand image, Price, Product Quality, Repurchase Interest